Pengaruh Kepemimpinan Transformasional, Kompensasi, dan Job Burnout terhadap Kinerja Karyawan - Fatimah Azzahra Ramadhini; Nurti Widayati (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to examine the effects of transformational leadership, compensation, and job burnout on employee performance. The object of this research is all the employee staffs of PT. Wahana Wirawan. The sample in this study were 78 staffs employee using purposive sampling method by distributing questionnaires. The data in this study were analyzed using multiple regression. The result obtained in this study indicate that transformational leadership and compensation affects employee performance in PT. Wahana Wirawan while ob burnout does not affect employee performance ini PT. Wahan Wirawab, it can be assumed that the quality of transformational leadership and compensation is already in a great condition and meet the comfort level to create great employee performance.